PEMIKIRAN POLITIK ISLAMISME MODERAT AL JAM’IYATUL WASHLIYAH - Ja'far Ja'far (UIN Raden Mas Said Surakarta, 2019)
Aljam’iyatul Washliyah is an Islamic organization in North Sumatra that has mass potential, business charity and social religion which is still ignored by many researchers. This study reveals the development of Alwashliyah's political thought in Indonesia. The process of extracting data is carried out from document studies and interviews with important figures in this organization. Alwashliyah's political thinking continues to experience development. Aljam’iyatul Wasliyah was born as a non-political organization because it was engaged in education, preaching and social charity. During the Old Order, Alwashliyah tried to become a special member of the Masyumi Party. Then, move to support Parmusi and have an ideological relationship with PPP. This study argues that Alwashliyah's political understanding is moderate Islamism. This organization supports Islam as the basis of the state by rejecting Pancasila. However, gradually this organization accepted Pancasila as the final ideology. This paper contributes to seeing how the political dynamics of a religious organization accommodate Pancasila